Missed marks: This is no longer the 20th century. (September 2021) - Hannud Abdo, Alexandre
Following an invitation by the editors of Social Science Information to react to an article by Olof Hallonsten, this article joins a debate about ways of evaluating science in our current context. This article presents an argument in support of the following four assertions and their importance to properly approach today the transformations of science evaluation and governance in the last decades: (a) scientific communities have failed to update their self-governance as societies transitioned from 'rural-labor societies' to 'urban-knowledge societies'; (b) the ensuing discrepancy from expectations contributed to the economization of science; (c) we must consider two distinct processes of democratization; and (d) geopolitics plays an important role in the establishment of commodification in wealthy nations.